(untitled) (Global Journal of Computer Science and Technology, 2014)
Component Based Development relies on already existing components to develop the system. It offers various advantages as increase in productivity, reduced development effort and time. The biggest challenge is to select the appropriate component from number of alternatives based on the quality parameters. In this paper COTS component selection is reduced to a multi criteria decision problem by quantifying it with PROMETHEE method. PROMETHEE is an outranking method which better supports the evaluation and selection from various alternatives based on the functional and non-functional requirements. The aim of this paper is to show the application of PROMETHEE in evaluating, analysing and selecting the appropriate COTS component with respect to requirements. The paper also discusses the procedure and benefits of using PROMETHEE method over the other MCDA methods.